USAGE OF UZBEK PROVERBS IN ABDULLA QODIRIY’S NOVEL “O’TKAN KUNLAR” - Usmonova Sevara Sultonovna; Solijonova Shahnoza Ikromjon qizi (TADQIQOTLAR.UZ, 2023)
Annotation: This article discusses the significant role of Uzbek proverbs in Abdullah Qodiriy 's classic novel "O'tgan kunlar" (The Days Gone By). The proverbs play a crucial role in shaping the narrative, adding depth to the characters and their interactions, and reflecting the rich cultural heritage of Uzbek society.